A Survey on Requirements Elicitation Practices Among Courseware Developers - Mohd Kasirun, Zarinah (Malaysian Journal of Computer Science, 2005)
Requirements elicitation in any application development has many important benefits. Due to this, it should be practiced in alignment to its objectives. This paper is based on the findings of a survey conducted among Malaysian courseware developers community. The paper starts with a definition of requirements elicitation and a description on how the survey was conducted. This is followed by the requirements elicitation practice as perceived by the respondents. Finally, a conclusion is drawn on the requirements elicitation practices and how to improve them.